A case of endocapillary proliferative glomerulonephritis with macrophages phagocytosing monoclonal immunoglobulin lambda light chain. (19th November 2014) - Watanabe, Hirofumi; Osawa, Yutaka; Goto, Shin; Habuka, Masato; Imai, Naofumi; Ito, Yumi; Hirose, Takayuki; Chou, Takaaki; Ohashi, Ryuji; Shimizu, Akira; Ehara, Takashi; Shimotori, Takashi; et al.
<x xml:space="preserve">Abstract</x> Multiple myeloma (MM) is a plasma‐cell neoplasm that can cause renal disorders. Renal lesions in MM can present with a very rare pathological manifestation involving a specific monoclonal immunoglobulin (Ig). We report the case of a 33‐year‐old woman who had edema, fatigue, elevated serum creatinine levels, hypoalbuminemia, and hypercholesterolemia. She had persistent hematuria and proteinuria lasting 3 years. Serum protein electrophoresis showed an M‐spike, and serum immunofixation demonstrated the presence of monoclonal IgG λ. She had proteinuria in the nephrotic range, and a monoclonal λ fragment was present on urine immunofixation. Renal biopsy showed proliferative glomerulonephritis with λ light chain and C3c deposition and inflammatory cell infiltration with CD68. Macrophage lysosomes contained λ light chains, suggesting their partial phagocytosis. She was diagnosed with symptomatic MM and was treated with bortezomib and dexamethasone and an autologous peripheral stem cell transplant conditioned with intravenous melphalan. She achieved a partial response with decreased serum monoclonal protein and improved renal function. This case may be categorized as a monoclonal gammopathy‐associated proliferative glomerulonephritis. The biopsy finding of partially phagocytosed Ig λ light chains by macrophages is very rare; this pathological condition is similar to crystal‐storing histiocytosis.